Red strain Oryza sativa-unpolished thai rice prevents oxidative stress and colorectal aberrant crypt foci formation in Rats - Tammasakchai,A. (Asian Pacific Organization for Cancer Prevention, 2015)
Oxidative stress has been proposed to be involved in colorectal cancer development. Many dark pigments of plants have potent oxidative stress preventive properties. In this study, unpolished Thai rice was assessed for antioxidant activity using 1,1-diphenyl-2-picrylhydrazyl (DPPH) and 2,2'-azinobis-3-ethylbenzothiazoline-6-sulfonic acid (ABTS) methods. Red strain unpolished Thai rice was also administered to rats exposed to azoxymethane (AOM) for induction of aberrant crypt foci (ACF). Serum malondialdehyde (MDA) and ferric reducing antioxidant power (FRAP) were investigated for cellular oxidative stress and serum antioxidants, respectively. Red pigment unpolished Thai rice demonstrated high antioxidant activity and was found to significantly and dose dependently decrease the total density and crypt multiplicity of ACF. Consumption of Thai rice further resulted in high serum antioxidant activity and low MDA cellular oxidative stress. Interestingly, the density of ACF was strongly related to MDA at r = 0.964, while it was inversely related with FRAP antioxidants (r = -0.915, p < 0.001). The results of this study suggest that the consumption of red strain of unpolished Thai rice may exert potentially beneficial effects on colorectal cancer through decrease in the level of oxidative stress.